"Old school" meets "new school": Using books and tablets to improve information literacy and promote integrative learning among business students. Issue 3 (November 2017) - Mang, Colin; Brown, Natalya; Piper, Linda
Abstract: This article discusses the use of Common Book and Tablet programs in post-secondary business education. We highlight methods by which each program enhances information literacy and integrative learning. We demonstrate how these programs can enhance students' communication and collaboration skills and enhance employability. We discuss classroom activities that both a Common Book and a Tablet can be used for as well as ways in which the programs offer mutual reinforcement to provide additional benefits during implementation. The article concludes with a discussion of obstacles to implementing either a Common Book or a Tablet program and methods to overcome those obstacles. Highlights: The concurrent implementation of Common Book and Tablet programs is evaluated. Each program can improve information literacy, integrative learning, and student engagement. Common Book and Tablet programs can be mutually reinforcing for added benefits. Faculty acceptance and budgetary constraints are barriers to both programs.